Pinocchio: hello friend (Hello friend India, 2010)
Pinocchio is a wooden puppet brought to life, yearning to become a real boy. He embarks on various adventures, often getting into trouble due to his curiosity and tendency to lie. With the help of his father, Geppetto, and the Blue Fairy, he learns important lessons about honesty and bravery.